Effectiveness of Starting Weaning at 4 Months Compared to 6 Months to Reduce Anemia among Infants: An Evidence-Based Case Report - Nadya Johanna; Taufik MS; Maulana MS; Samban JLT; Nurul Ratna Manikam (Indonesian Nutrition Association, 2018)
Aim: Comparing the effectiveness of introducing complementary foods at four months of age compared to six months of age to reduce the incidence of iron-deficiency anemia among healthy full-term infants.Methods: A systematic search was conducted on PubMed, EBSCO, and Cochrane on 28th September 2017. After the selection of title and abstract was done using the predefined inclusion and exclusion criteria. Twelve original articles were found, but after full-text assessment, only two studies were considered relevant. These two studies were further critically appraised for its validity, importance, and applicability to measure its usability degree in this study.Results: These two included studies showed no significant difference of iron-deficiency anemia incidence between the two complementary feeding groups. This can be shown by the absolute risk reduction which varied from -3.1% to 13.4%, relative risk reduction which varied from -22.8% to 18.4%, and number needed to treat which varied from -33 to 8. Both studies found that the ferritin was significantly different between both groups. However, the hemoglobin concentration was significantly higher in the complementary fed group in only one study.Conclusion: The introduction of complementary feeding at 4 months of age is not effective to reduce the incidence of iron-deficiency anemia.